Figure 1 from: Svensson M, Ekman S, Klepsland JT, Nordin A, Thor G, von Hirschheydt G, Jonsson F, Knutsson T, Lif M, Spribille T, Westberg M (2017) Taxonomic novelties and new records of Fennoscandian crustose lichens. MycoKeys 25: 51-86. https://doi.org/10.3897/mycokeys.25.13375 - Svensson, Måns; Ekman, Stefan; Klepsland, Jon T.; Nordin, Anders; Thor, Göran; von Hirschheydt, Gesa; Jonsson, Fredrik; Knutsson, Tommy; Lif, Mattias; Spribille, Toby; Westberg, Martin (Zenodo, 2017)
Figure 1 - A–B Bacidia pycnidiata (UPS L-681835), A group of apothecia B pycnidia with long and curved necks. C–D Bacidina adastra, C close-up of thallus with apothecia, note intermingled black fibers belonging to the polypropylene fabric on which the specimen grows (UPS L-779918) D overview of thick, sterile thallus (UPS L-779932). Scale bars: 0.25 mm (A–B), 1 mm (C–D).